First in human implantation of the mechanical expanding Lotus® valve in degenerated surgical valves in mitral position. Issue 7 (21st September 2015) - Schaefer, Ulrich; Conradi, Lenard; Lubos, Edith; Deuschl, Florian; Schofer, Niklas; Seiffert, Moritz; Treede, Hendrik; Schirmer, Johannes; Reichenspurner, Hermann; Blankenberg, Stefan
Abstract : Introduction: Implantation of transcatheter heart valves (THV) into degenerated surgical valves is an emerging therapy for selected high‐risk patients. Although, CE mark of most THV is limited for native aortic valvular stenosis, transcatheter valve implantation into degenerated bioprostheses, even in mitral position is very intriguing. Methods and Results: After placement of a cerebral protection device (Claret Sentinel®), three consecutive patients (age, 79.0 ± 6.1; log EuroSCORE I: 33.3 ± 9.2%) with a degenerated mitral bioprosthesis were treated by transapical implantation of the Lotus® valve (Boston Scientific Inc.). In addition, a SwanGanz catheter was introduced in the pulmonary artery for hemodynamic assessments all patients. Procedural success was 100%. Valve implantation was performed without rapid ventricular pacing. Resheating was performed in two patients due to suboptimal initial positioning. Invasive online hemodynamics revealed stable blood pressure in all patients. After Lotus® valve implantation, valvular mitral regurgitation was completely eliminated in all patients. One patient had a mild paravalvular leak of the surgical bioprosthesis, which was present before implantation. Invasive right and left heart hemodynamics showed an immediate improvement after Lotus® valve implantation. Mean mitral surface area (2.1 ± 0.2 cm 2 ) and mean gradient (3.7 ± 2.1 mm Hg) demonstrated satisfactory results. All patients were immediately extubated and discharged from the hospital without any adverse event. Conclusions: This study demonstrates for the first time the feasibility of transapical Lotus® Valve implantation in degenerated mitral bioprostheses. The controlled mechanical Lotus® valve expansion with remarkably stable hemodynamics throughout the procedure offers a new and valuable treatment option. © 2015 Wiley Periodicals, Inc.